Enhancement of biocompatibility of anodic nanotube structures on biomedical Ti–6Al–4V alloy via ultrathin TiO2 coatings - Sepúlveda, Marcela; Capek, Jan; Baishya, Kaushik; Rodriguez-Pereira, Jhonatan; Bacova, Jana; Jelinkova, Stepanka; Zazpe, Raul; Sopha, Hanna; Rousar, Tomas; Macak, Jan M. (Frontiers in Bioengineering and Biotechnology, 2024)
This work aims to describe the effect of the surface modification of TiO2 nanotube (TNT) layers on Ti-6Al-4V (TiAlV) alloy by ultrathin TiO2 coatings prepared via Atomic Layer Deposition (ALD) on the growth of MG-63 osteoblastic cells. The TNT layers with two distinctly different inner diameters, namely ~15 nm and ~50 nm, were prepared via anodic oxidation of the TiAlV alloy. Flat, i.e., nonanodized, TiAlV alloy foils were used as reference substrates. Additionally, a part of the TNT layers and alloy foils was coated with ultrathin coatings of TiO2 by ALD. The number of TiO2 ALD cycles used was 1 and 5 cycles leading to a nominal TiO2 thickness of ~0.055 and ~0.3 nm, respectively. The ultrathin TiO2 coating by ALD enabled to optimize the surface hydrophilicity for optimal cell growth. In addition, coatings shaded impurities of V-and F-based species (stemming from the alloy and the anodization electrolyte) that affect the biocompatibility of the tested materials while preserving the original structure and morphology. The evaluation of the biocompatibility before and after TiO2 ALD coating on TiAlV flat surfaces and TNT layers was carried out using MG-63 osteoblastic cells and compared after incubation for up to 96 h. The cell growth, adhesion, and